Internal Controls in the System Accounting Information - Jannah, Miftahul; Hazmi, Yusri; Fitri, Nabila Jannatun; Ashar, M. Haris (West Science Accounting and Finance, 2024)
accounting information system functions as a framework for implementing accounting processes within the organization. It is important to have adequate safeguards in place in the accounting process to prevent unintentional and intentional errors and anomalies in financial statements. This article was written using descriptive techniques, which mostly rely on library data. This article shows that financial reports, which function as a form of organizational management accountability to interested parties, must be ensured to be free from errors. In this scenario, internal controls play an important role in achieving the desired results, in addition to other considerations such as audits carried out by public accountants.